PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA GURU TERHADAP DISIPLIN KERJA - Umami, Siti; Lian, Bukman; Missriani, Missriani (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
The objective of the study was to know, 1) the influence of leadership on discipline, 2) the influence of the motivation on discipline, and 3) The influence of the leardership and motivation on discipline. This research uses quantitative methods. The population was the all teacher at State Junior High School 1 of Tanjung Raja. The sample taken by totalling sampling with the total 35 teachers. Data collection is done by questionnaire, and documentation. Data were analyzed descriptively using SPSS version 16 for windows. From the results of this study it can be concluded that 1) there was an influence of the leaderhip on discipline, 2) there was an influence of motivation on discipline, 3) there was significant influence between leadership and motivation on discipline.